Efficient dynamic DNA-based block cipher algorithm - Chng, Chern Wei (2023)
The significance of block cipher algorithms lies in their versatility and resilience. They possess a wide range of applications, spanning from guaranteeing the security of web traffic through protocols like SSL/TLS to encrypting confidential data stored on hard drives. Block ciphers are designed with a specific focus on maximising speed and efficiency, making them highly suitable for use in both hardware and software systems. Ensuring sufficient non-linearity is a crucial factor in the design of S-Box. The use of non-linear S-Box is essential in preventing linear approximations that could lead to successful attacks, such as differential cryptanalysis. This form of assault exploits the correlations between changes in the input and their effects on the output. When an S-box displays a high degree of linearity, it becomes vulnerable to these assaults, hence undermining the security of the cipher and making it easier to decipher. ShiftRow and MixColumns are essential for achieving the required dispersion and obfuscation in a safe block cipher. Nevertheless, they provide unique challenges in relation to security. Consequently, a Dynamic DNA-based S-box was proposed to enhance the nonlinearity of the S-Box. The utilisation of four sets of 4 x 4 S-Box structures contributes to the simplicity and stability of the S-Box construction. The proposed method involves utilising DNA-based components consisting of the nucleotides {A, T, G, C} to generate a novel Dynamic DNA-based S-Box. The suggested method enhances the non-linearity of the S-Box, offering a dynamic solution that effectively defends against linear and differential cryptanalysis. Additionally, a DNA-based ShiftRow function was proposed to enhance the execution of permutation by methodically displacing the rows of the state array using different offset values. This outcome is characterised by a linear procedure and lacks the ability to combine data from multiple rows. The suggested ShiftRows algorithm utilises DNA-specific characteristics of the nucleotides {A, T, G, C}. The ShiftRow operation in this system, which is based on DNA, operates as a pseudo-random number generator. It generates encrypted random numbers for the encryption process. To guarantee that the random numbers generated by this DNA-based block cipher satisfy particular requirements and specifications, all values and parameters will conform to the standards established by the National Institute of Standards and Technology (NIST). Moreover, a DNA-based MixColumns function was proposed to enhance the linear transformation executed in a finite field by employing fixed polynomials and preventing vulnerability to linear and differential attacks. The proposed MixColumns operation is designed to incorporate the unique characteristics of DNA, specifically the nucleotides {A, T, G, C}. The DNA-based MixColumns operation functions as a pseudo-random number generator, generating an encrypted random number for the purpose of encryption. In order to guarantee that the random numbers produced by the suggested DNA-based block cipher satisfy the necessary criteria, all values and parameters will conform to the requirements established by the National Institute of Standards and Technology (NIST). Finally, the findings confirm that the proposed approaches have demonstrated enhancements, such as passing the randomness test, exhibiting the avalanche effect, and withstanding cryptanalysis. In general, the research has demonstrated encouraging evidence of the DNA-based block cipher's ability to enhance security and withstand linear and differential attacks.